Health-Based Weight Stereotypes in Advertising: Perpetuating Unhealthy Responses among Overweight Identifiers. Issue 2 (8th January 2021) - Connors, Scott; Spangenberg, Katie; Perkins, Andrew; Forehand, Mark
Abstract: In this research, we identify health-based weight stereotypes in advertising and demonstrate that they can perpetuate unhealthy outcomes within overweight populations. We show that advertisements featuring thin models and healthy (versus unhealthy) products lead to greater product–model fit, which leads consumers to view the advertisements more favorably. In contrast, for advertisements featuring overweight models and unhealthy (versus healthy) products, only overweight identifiers perceive higher levels of product–model fit leading to more favorable evaluations, perpetuating unhealthy consumption behaviors. In light of this concerning finding, we develop an actionable advertising strategy that better frames advertisements featuring overweight models to increase overweight consumers' likelihood of purchasing healthy products.